1999
DOI: 10.1039/a807129b
|View full text |Cite
|
Sign up to set email alerts
|

EPR investigation of HO/ radical initiated degradation reactions of sulfonated aromatics as model compounds for fuel cell proton conducting membranes

Abstract: In order to predict hydroxy radical initiated degradation of new proton conducting polymer membranes based on polystyrene, polyethersulfone, polyetheretherketone, or on polymers obtained by radiation grafting of styrene on different fluoropolymers, eight sulfonated aromatics were chosen as model compounds for EPR experiments, aiming at the identification of products of HO• radical reactions with these polymers. Photolysis of H 2 O 2 was employed as the source of hydroxyl radicals. A detailed investigation of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
214
2

Year Published

2005
2005
2010
2010

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 321 publications
(221 citation statements)
references
References 56 publications
5
214
2
Order By: Relevance
“…5) At high in situ pH, the oxidative radical mechanism for polymer degradation is suppressed [10] and potentially enables the use of hydrocarbon only membranes (C-H backbone) with enhanced green credentials (manufacturing and disposal)…”
Section: )mentioning
confidence: 99%
“…5) At high in situ pH, the oxidative radical mechanism for polymer degradation is suppressed [10] and potentially enables the use of hydrocarbon only membranes (C-H backbone) with enhanced green credentials (manufacturing and disposal)…”
Section: )mentioning
confidence: 99%
“…2058 R. Koch et al: Reaction of the OH-adducts of aromatics with NO, NO 2 and O 2 of H 2 O. Hübner and Roduner (1999) studied hydroxylation of p-methoxy-benzenesulphonate and observed various phenoxyl radical anions, i.e. the ether link was broken.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the performance loss of the MEA was attributed to the degradation of the cathode catalyst. Regarding the corrosion mechanism of the carbon support, Hubner et al reported on the "Hydroxyl radical initiated degradation reactions of sulfonated aromatics for fuel cell membrane" (22). They reported that the hydroxyl radical addition occurs on the aromatic ring, and is followed by the addition of an oxygen molecule.…”
Section: Analyses Of the Npc Mea Operated At 120ºc For 4000 Hoursmentioning
confidence: 99%